Do conventional glass ionomer cements release more fluoride than resin-modified glass ionomer cements? - Maria Fernanda Costa Cabral; Roberto Luiz de Menezes Martinho; Manoel Valcácio Guedes-Neto; Maria Augusta Bessa Rebelo; Danielson Guedes Pontes; Flávia Cohen-Carneiro (Korean Academy of Conservative Dentistry, 2015)
Objectives The aim of this study was to evaluate the fluoride release of conventional glass ionomer cements (GICs) and resin-modified GICs. Materials and Methods The cements were grouped as follows: G1 (Vidrion R, SS White), G2 (Vitro Fil, DFL), G3 (Vitro Molar, DFL), G4 (Bioglass R, Biodinâmica), and G5 (Ketac Fil, 3M ESPE), as conventional GICs, and G6 (Vitremer, 3M ESPE), G7 (Vitro Fil LC, DFL), and G8 (Resiglass, Biodinâmica) as resin-modified GICs. Six specimens (8.60 mm in diameter; 1.65 mm in thickness) of each material were prepared using a stainless steel mold. The specimens were immersed in a demineralizing solution (pH 4.3) for 6 hr and a remineralizing solution (pH 7.0) for 18 hr a day. The fluoride ions were measured for 15 days. Analysis of variance (ANOVA) and Tukey's test with 5% significance were applied. Results The highest amounts of fluoride release were found during the first 24 hr for all cements, decreasing abruptly on day 2, and reaching gradually decreasing levels on day 7. Based on these results, the decreasing scale of fluoride release was as follows: G2 > G3 > G8 = G4 = G7 > G6 = G1 > G5 (p < 0.05). Conclusions There were wide variations among the materials in terms of the cumulative amount of fluoride ion released, and the amount of fluoride release could not be attributed to the category of cement, that is, conventional GICs or resin-modified GICs.